Faktor-Faktor Yang Mempengaruhi Minat Siswa Dalam Kegiatan Pengembangan Diri Seni Tari Di SMP Negeri 9 Payakumbuh - Intan Kumala Sari; Afifah Asriati (FBS Universitas Negeri Padang, 2020)
This study aims to determine and describe the factors that influence students' interest in dance self-development activity in SMP Negeri 9 Payakumbuh. Type of this research was qualitative research. The research instrument was the researcher. It was also assisted by using stationery, recording equipment and camera. Types of data in this study were primary and secondary data. Techniques of data collection were carried out by taking literature study, observation, interviews and documentation. The steps in analyzing data were done by doing collection, reduction, presentation, drawing conclusions of data. The results show that the factors that influence students' interest in dance self-development activity in SMP Negeri 9 Payakumbuh are found internally and externally. Internal factors are such as the lack of attention of the Students in dance self-development, the students' attitudes tend to be low, the ability of students overally are very good and the students’ motivation are also very good. Meanwhile, external factors include the teacher, infrastructures and the learning method. So it can be concluded that the attention, attitude, ability, motivation of students are very influential in the dance self-developement activity.